Distribution Of Covid-19 Based on Location Quotient (LQ) in Batang Regency, Central Java, Indonesia - Heni Isniyati; Eram Tunggul Pawenang; Mustafa Daru Affandi; Yanesti Nuravianda Lestari (Unnes Journal of Public Health, 2023)
The distribution of Covid-19 cases in the Batang regency increased to 9,924 confirmed cases from its first identification on April 4, 2020, until December 2021. The potential distribution of Covid-19 instances in 2020 and 2021 is in low land near the regency's main road access. This study aims to analyze the potential distribution of Covid-19 in an area based on environmental characteristics by a spatial approach based on location quotient (LQ) in the Batang regency for 2 consecutive years. The type of research is descriptive with a spatial explanatory design with a sample were 248 villages in the Batang regency. The results showed that 248 villages were confirmed to have Covid-19 with a very high potential distribution (LQ> 1.2) were 53 (21.4%) villages, the high potential distribution (1.05<LQ< 1.2) were 20 (8,1%) villages, the average potential distribution (0.95<LQ< 1.05) were 12 (4,8%) villages, the low potential distribution (0.80<LQ< 0.95) were 25 (10,1%) villages, and shallow potential distribution (0<LQ< 0.8) were 138 (55,6%) villages. Moran’s index showed that the pattern of Covid-19 has a significant spatial correlation with p-value < 0.01 and Z-score > 2.58 in both 2020 and 2021 with the distribution pattern forming a cluster.